Electromagnetic shielding effectiveness of polyester fabrics with polyaniline deposition - USTA, İSMAİL (SAGE PUBLICATIONS LTD, 2014)
In this study, conductive fabrics were developed by polymerizing aniline onto polyester (PET) woven fabrics. The fabric treatment was carried out by the chemical polymerization method at 0.5 M, 0.8 M and 1.2 M aniline concentrations. Hydrochloric acid as acidic medium and ammonium persulfate as oxidant were employed during the polymerization process. The polyaniline (PANI)-treated PET fabric structures were fully characterized and evaluated in terms of their electromagnetic shielding effectiveness, absorption and reflection characteristics, and tensile properties. Additionally, the fabrics were examined by scanning electron microscopy for their surface morphology and Fourier transform infrared spectroscopy for their chemical functionality. The electromagnetic shielding effectiveness and absorption and reflection characteristics were determined using a network analyzer with a frequency range from 15 MHz to 3000 MHz. The electrical characteristics were measured by the two-end method. It was concluded that the tensile strength values of the treated fabrics were enhanced when the amount of monomer in the concentrations increased as compared to the untreated fabrics. It is interesting to note that 1.2M treated fabric had the lowest tensile strength values as compared to the other treated fabrics. It was also found that a 0.5M concentration of PANI-treated fabric had the lowest surface resistivity since it showed the highest conductivity value. Another important finding is that the 0.8M aniline-treated fabric had the highest shielding effectiveness.
Keywords: Polyaniline; polyester fabric; conductive textile; electromagnetic shielding; chemical polymerization; FREQUENCY-RANGE; COATED FABRICS; COMPOSITE; FILMS; CONDUCTIVITY; FIBERS